2020
DOI: 10.1021/acs.jpcc.9b10621
|View full text |Cite
|
Sign up to set email alerts
|

Photocarrier Recombination Dynamics in BiVO4 for Visible Light-Driven Water Oxidation

Abstract: Photocarrier recombination dynamics of BiVO4 powders synthesized at different temperatures were studied by temperature-dependent steady-state and time-resolved photoluminescence (PL). Structural analysis indicates that BiVO4 materials synthesized at low temperatures contain mixed-phase crystals including monoclinic and tetragonal scheelite phase, showing poor photocatalytic performance. Relatively higher synthesis temperatures improve the photocatalyst efficiency by promoting the formation of single-phase mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
4
18
0
Order By: Relevance
“…To characterize the effect of the Zr additive on photoexcited charge recombination in BVO, the steady-state and time-dependent PL were measured for undoped and doped samples. No bandto-band emission (expected ∼2.4 eV) is observed, but a broad pronounced emission peak centered at ∼1.85 eV is detected (Figure 3a), consistent with our previous report 26 and other works. 27−30 Based on our previous study, the observed PL emission is due to donor−acceptor pair (DAP) transitions from a deep donor at 0.58 eV below the conduction band (CB) into a shallow acceptor at 0.1 eV above the valence band (VB).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To characterize the effect of the Zr additive on photoexcited charge recombination in BVO, the steady-state and time-dependent PL were measured for undoped and doped samples. No bandto-band emission (expected ∼2.4 eV) is observed, but a broad pronounced emission peak centered at ∼1.85 eV is detected (Figure 3a), consistent with our previous report 26 and other works. 27−30 Based on our previous study, the observed PL emission is due to donor−acceptor pair (DAP) transitions from a deep donor at 0.58 eV below the conduction band (CB) into a shallow acceptor at 0.1 eV above the valence band (VB).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Fitted TRPL parameters are summarized in Table S2. All observed lifetimes are far behind the ideal radiative lifetime, τ r , of 6 μs estimated using the van Roosbroeck–Shockley relation for BVO . The results suggest that photoexcited charges predominately recombine nonradiatively (τ PL ≈ τ nr ), likely via the Shockley Read Hall (SRH) recombination.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…3,4 More and more strategies have been conducted to improve photocatalytic efficiencies. 5,6 Rare-earth (RE) ion doping is effective in optimizing photocatalysis via a narrowing band gap, extending absorption, modifying band position, and promoting charge carrier separation. 7−9 RE elements with an incompletely occupied 4f orbital can increase the optical absorption and separate the photogenerated charges.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photoenergy conversion is one of the most popular topics in the development of functional materials, which usually has two kinds of well-known behaviors, photoluminescence and photocatalysis. Photoluminescence investigation has a long history in lighting and displays; , however, photocatalysis is still not developed in practical applications because of the fast electron–hole recombination in a semiconductor photocatalyst. , More and more strategies have been conducted to improve photocatalytic efficiencies. , Rare-earth (RE) ion doping is effective in optimizing photocatalysis via a narrowing band gap, extending absorption, modifying band position, and promoting charge carrier separation. RE elements with an incompletely occupied 4f orbital can increase the optical absorption and separate the photogenerated charges. , Among them, the Eu 3+ ion is a good candidate widely used in photocatalysts because of its highly active optical activities. For example, Eu 3+ -doped TiO 2 photocatalysts with enhanced photocatalysis have been widely reported. …”
Section: Introductionmentioning
confidence: 99%